2009
DOI: 10.1039/b905444h
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reaction temperature on the oscillatory behaviour in the palladium-catalysed phenylacetylene oxidative carbonylation reaction

Abstract: This paper reports the influence of reaction temperature on the occurrence and characteristics of pH oscillations that are observed during the palladium-catalysed phenylacetylene oxidative carbonylation reaction in a catalytic system (PdI2, KI, air, NaOAc) in methanol. Isothermal experiments were performed over the temperature range 10-50 degrees C. The experiments demonstrate that oscillations occur in the range 10-40 degrees C and that a decrease in reaction temperature results in an increase in the period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 14 publications
7
38
3
Order By: Relevance
“…Previous studies of the PCPOC reaction at temperatures from 0 to 40°C found that changing the reaction temperature produced changes in the shape of the pH oscillations [7,12]. Increasing the water content of the reaction also affects the shape of the pH oscillations as shown in Table 3.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies of the PCPOC reaction at temperatures from 0 to 40°C found that changing the reaction temperature produced changes in the shape of the pH oscillations [7,12]. Increasing the water content of the reaction also affects the shape of the pH oscillations as shown in Table 3.…”
Section: Resultsmentioning
confidence: 78%
“…3d). As reactions where conducted in a reaction calorimeter, it was possible to apply power compensation calorimetry to record changes in reaction heat over time [7,12,13,16]. Oscillations in heater power were still evident with 5, 20 and 30% water, were in phase with the pH oscillations and reflected the changes in the pH oscillations as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is revealed that this oscillatory system does not require an external oxidizing agent in order for catalyst recycling to occur. Furthermore, oscillatory behavior is recorded using considerably lower concentrations of both PdI 2 (approximately fivefold) and phenylacetylene (approximately 40-80-fold) compared to those reported previously [9][10][11]17]. As a result, the transparency of the reaction solution is significantly increased.…”
Section: Introductionmentioning
confidence: 62%
“…The pH then exhibits a steady rise over a period of 600 min after which stable oscillations in pH commence. The induction period observed prior to entering the oscillatory region is considerably shorter than the 2,000 min recorded previously at similar temperatures [17]. Temkin and co-workers [6,8] were able to achieve oscillations in pH within minutes of starting a PCPOC reaction, however they reported an experimental setup using mixed gases (CO/O 2 ) and higher reaction temperatures (40°C).…”
Section: Resultsmentioning
confidence: 83%